Chronic kidney disease in older patients: the contribution of kidney pathology to the estimated glomerular filtration - E. V. Efremova; A. M. Shutov; T. S. Kuznetsovа (Архивъ внутренней медицины, 2024)
The purpose of the study was to assess the contribution of kidney pathology to the estimated glomerular filtration rate and its prognostic value in elderly and senile patients.Materials and methods. 472 elderly and senile age patients (241 women and 231 men, mean age 69.6±7.3 years) with stable cardiovascular diseases were examined. CKD was observed in 302 (63.9 %) elderly and senile patients. Estimated glomerular filtration rate (eGFR) was determined using the CKD-EPI equation (modified 2011). The contribution of kidney pathology (CKP) to eGFR was calculated by the difference between the “real” eGFR (calculated using the CKD-EPI, 2011 formula based on the “real” serum creatinine) and the predicted eGFR for a given age and sex (patent No. RU 2723748 C1). The follow-up period was 12 months. The primary endpoint was overall mortality.Results. The CKP in eGFR in elderly and senile patients was 26.3 (14.9;35.7) %, increasing with the severity of CKD. The CKP in eGFR in elderly and senile patients with CKD did not differ depending on gender and age (p>0.05). The modified Charlson comorbidity index was higher in patients with CKD with CKP in eGFR more than 43.3 % compared to patients with The CKP in eGFR less than 43.3 (p = 0.004). The CKP in eGFR more than 43.3 % was associated with a 1-year risk of death in patients with CKD (OR 4.7; 95 % CI 1.99–10.9; p<0.0001). When assessing the prognostic value of CKP in eGFR, regardless of the CKD it was found that an increase CKP in eGFR more than 17.9 % was associated with a 1-year risk of death in elderly and senile patients with stable cardiovascular diseases (OR 2.47; 95 % CI 1.31–4.67; p=0.004).Conclusion. The CKP in eGFR in elderly and senile patients with CKD and stable cardiovascular comorbidity increases with the severity of CKD and does not depend on gender and age. In elderly and senile patients with stable cardiovascular diseases, the CKP in eGFR has prognostic advantages when assessing annual mortality compared to eGFR assessment using the CKD EPI formula (2011).